Autophagy of the ER Requires Actin Assembly Driven by the Interaction of ER with Endocytic Pits - Peter Novick; Dongmei Liu; Susan Ferro-Novick (Contact, 2022)
Autophagy of the cortical ER in budding yeast was unexpectedly found to require End3, a component of the endocytic machinery that promotes the assembly of actin at endocytic pits on the plasma membrane. The cortical ER transiently interacts with invaginating endocytic pits through a linkage consisting of VAP proteins, oxysterol binding proteins and type I myosins. These proteins are required for actin assembly and for autophagy of the ER. Assembly of actin at these contact sites may direct the movement of ER away from the cortex towards sites of autophagosome assembly.